Frequency-dependent signal transmission and modulation by neuromodulators - Ito, Hiroshi T.; Schuman, Erin M. (Frontiers in Neuroscience, 2008)
The brain uses a strategy of labor division, which may allow it to accomplish more elaborate and complicated tasks, but in turn, imposes a requirement for central control to integrate information among different brain areas. Anatomically, the divergence of long-range neuromodulator projections appears well-suited to coordinate communication between brain areas. Oscillatory brain activity is a prominent feature of neural transmission. Thus, the ability of neuromodulators to modulate signal transmission in a frequency-dependent manner adds an additional level of regulation. Here, we review the significance of frequency-dependent signal modulation in brain function and how a neuronal network can possess such properties. We also describe how a neuromodulator, dopamine, changes frequency-dependent signal transmission, controlling information flow from the entorhinal cortex to the hippocampus.